‘Maybe I will give some help…. maybe not to help the eyes but different help’: an analysis of care and support of children with visual impairment in community settings in Malawi - Gladstone, M.; McLinden, M.; Douglas, G.; Jolley, E.; Schmidt, E.; Chimoyo, J.; Magombo, H.; Lynch, P. (Child : care, health & development, 2017)
Background Visual impairment in children is common in low and middle‐income settings. Whilst visual impairment (VI) can impact on the development of children, many reach full potential with appropriate early intervention programmes. Although there is increased emphasis on early child development globally, it is not yet clear how to provide specific programmes for children with VI in low and middle‐income settings. This study aims to identify facilitators and barriers to the provision of a developmental stimulation programme for children with VI in rural and urban Malawi. Methods We undertook 6 focus groups, 10 home observations and 20 in‐depth interviews with carers of children with VI under 6 years in urban and rural Southern Malawi. We utilised topic guides relating to care, play, communication and feeding. Qualitative data were subject to thematic analysis that included placing themes within Bronfenbrenner's ecological framework. We established authenticity of themes through feedback from participants. Results We identified themes within Bronfenbrenner's framework at five levels: (1) blindness acting as a barrier to stimulation and communication, health and complex needs all affecting the individual child; (2) understanding of VI, ability to be responsive at the microsystem level of the carer; (3) support from other carers at microsystem level within a mesosystem; (4) support from other professionals (knowledge of, identification and management of children with VI, responsibilities and gender roles, environmental safety and prejudice, stigma and child protection all at the level of the exosystem. Discussion This study has revealed the requirements needed in order to produce meaningful and appropriate programmes to support nutrition, care and early stimulation for children with VI in this and similar African settings. This includes supporting carers to understand their child's developmental needs, how to better communicate with, feed and stimulate their child; offering advice sensitive to carers' responsibilities and professional training to better support carers and challenge community stigma.